From my cold, dead hands : Charlton Heston and American politics - Raymond, Emilie, 1973- (University Press of Kentucky, 2006)
Charlton Heston is perhaps most famous for his portrayal of Moses in Cecil B. DeMille's epic The Ten Commandments and for his Academy Award-winning performance in the 1959 classic Ben-Hur. Throughout his long career, Heston used his cinematic status as a powerful moral force to effect social and political change. "From My Cold, Dead Hands" examines how Heston evolved into a major American political figure. Heston has campaigned for both Democratic and Republican candidates, marched in support of black civil rights, served as the president of the Screen Actors Guild, helped shape policy for the